Future tense : how we made artificial intelligence -- and how it will change everything - Brockenbrough, Martha (Feiwel and Friends, an imprint of Macmillan Publishing Group, LLC, 2024)
"In this non-fiction book for teens, readers are guided through the development of this world-changing technology, exploring how AI has touched every corner of our world, including education, healthcare, work, politics, war, international relations, and even romance. This is essential reading for anyone who wants to understand how artificial intelligence got here, how to make the best use of it, and how we can expect it to transform our lives"--